2021
DOI: 10.1371/journal.pone.0254214
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods evaluation of the uptake of novel differentiated ART delivery models in a national sample of health facilities in Uganda

Abstract: Introduction Since 2017, Uganda has been implementing five differentiated antiretroviral therapy (ART) delivery models to improve the quality of HIV care and to achieve health-system efficiencies. Community-based models include Community Client-Led ART Delivery and Community Drug Distribution Points. Facility-based models include Fast Track Drug Refill, Facility Based Group and Facility Based Individual Management. We set out to assess the extent of uptake of these ART delivery models and to describe barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Studies on patient preferences between community‐ and clinic‐based ART delivery have found clinic‐based services to be favoured, especially in urban settings [ 44 , 45 , 46 , 47 ]. In Johannesburg adherence clubs, patients were more likely to recommend joining if they were in clinic‐ versus community‐based clubs [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on patient preferences between community‐ and clinic‐based ART delivery have found clinic‐based services to be favoured, especially in urban settings [ 44 , 45 , 46 , 47 ]. In Johannesburg adherence clubs, patients were more likely to recommend joining if they were in clinic‐ versus community‐based clubs [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…While we found overall little difference in clinical outcomes for reduced visit frequency, there are other potential benefits of reduced visits, including decongestion of health facilities, reduced provider workload, prioritization of care for new or clinically unstable PLWH, and reduced transmission of COVID-19 in health centers [ 5 , 13 , 41 44 ]. Reducing visit frequency has been reported to be one of the easiest DSD models to implement and aligns strongly with the care preferences of PLWH by reducing the economic costs of attending frequent appointments, reducing stigma, and allowing PLWH to normalize HIV [ 3 , 4 , 10 , 11 , 45 , 46 ]. HIV services, however, need to remain flexible enough to accommodate return to facilities for those who opt back into standard care or when clinical requirements change [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV services, however, need to remain flexible enough to accommodate return to facilities for those who opt back into standard care or when clinical requirements change [ 27 ]. Further research is needed to develop strategies that allow for transition between models of care and provide psychosocial support between extended visits (e.g., virtual visits or group models) [ 3 , 47 ]. As many countries, in response to COVID-19, have expanded multi-month dispensing for patients who have not previously been considered established on ART [ 12 ], it will be essential to explore outcomes in those less “established” on ART, as well as to develop strategies to align and integrate non-communicable disease care with these models and to identify optimum models of care for key populations, other regions, and children, to ensure the utility of these models for all PLWH [ 5 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations